Penerapan Media Pembelajaran berbasis Macromedia Flash dalam meningkatkan hasil Belajar Matematika Siswa Kelas X di SMK Penerbangan Techno Terapan Makassar - Mulyati Mulyati (STKIP Paris Barantai, 2019)
The type of this research is Classroom Action Research, the purpose of this study, is to improve the mathematics learning outcomes of class X students at the Applied Techno Flight Vocational School of Makassar through Macromedia Flash-based Learning Media. having its address at Jl. Sanrangan, No. 24 Makassar 2017/2018 school year. As for the subjects of this study were X class students totaling 28 students, consisting of 8 men and 20 women. This research was conducted in two cycles. The data collection techniques used in the study were 1) Data on student learning outcomes were taken through tests of learning outcomes given to students in each cycle. (2) Data on the implementation of learning with macromedia flash learning media is taken through observation sheets of student activities and observation sheets of learning management activities through the macromedia flash media. Data Analysis Techniques that are used are descriptive data analysis by giving an overview of student learning outcomes through tests and observation sheets on each cycle. The types of data collected in this study are quantitative data for student learning outcomes and qualitative data for student activities in learning and student response data to learning with flash macromedia media ... As for the results of this study are (a) Learning outcomes of class X SMK Techno Makassar flights can be improved through the application of media learning media macromedia flash (2) Learning through the application of learning media to macromedia flash learning media can increase the active role of students in the learning process. Keywords: learning outcomes, macromedia Flash.